Faktor-Faktor Yang Mempengaruhi Perubahan Laba Pada PT. Wijaya Karya Bangunan Gedung Tbk. Yang Terdaftar Di Bursa Efek Indonesia - Kannapadang, Dwibin; Ta’dung, Yohanis Lotong (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Competition in the business world, which is getting tighter and tighter so fast, has a huge impact on the development of the current capital market, especially in the business activities of large and small industries. This study aims to determine the effect of Current Ratio (CR), Debt to Equity Ratio (DER), Return On Assets (ROA), and Total Asset Turn Over (TATO) on changes in profits at PT. Wijaya Karya Gedung Tbk. Methods of data used is secondary data. The data analysis technique used in this study was multipke linear regression analysis using the SPSS version 24 statistical calculator. The results showed that the current ratio has positive effect on changes in earnings. Meanwhile, Debt to equity ratio (DER), Return on assets (ROA) and Total asset turnover (TATO) have no significant effect on changes in earnings.The coefficient of determination R Square is 0,816 indicating that changes in PT. Wijaya Karya Gedung, Tbk is determined by the current ratio, debt to equity ratio, return on assets, and total asset turnover of 81,6%, while the remaining 18,4% is determined by other factors outside the independent variabes in this study.